Microseismic Signals In The Obs Meramex Data Recording - Gatot, Yuliyanto (Physics Department Sebelas Maret University, 2011)
In order to detennine the frequency content especially microseismic in the data recording of ocean bottom seismo graph Meramex; an analysis has been conducted by comparing the OBS data recording when earthquakes occured with local and regional distants (6") on 27 and 28 June 2004, and also the comparison with the seismograph signal on the land. The analysis is conducted by processing the amplitude spectra from the data recording using geopsy software. The result obtained from the analysis is that the characteristic frequency content in the OBS is dominated by the maximum amplitude-: t-fr.:q ;ency 0.15 Hz for both data with and without earthquake event, whereas from the earthquake data recording station on the land (Al3 and AJI) drew a result on the peak amplitudo at the frequency about 0.3 Hz. or in the other words, the seismic recording data both in the station and OBS have the peak frequency which is near the microseismic peak frequency.